Himaya panitikan ng pagbabanyuhay - Himaya : Panitikan ng Pagbabanyuhay Online March 25-26, 2022; Arriola, Joyce L. (Manila National Commission for Culture and the Arts, 2022)
On reflection and movement of the spirit in writing and reading literature in time of crisis during Covid and after in the Philippines; papers of a conference.
Part II: Literature after CoVID Bulan, bungas, balanaks, bamboos, and banana stalks: "white as beautiful" and the resistance to the idea of Filipino colonial metality in Alcina's historia and other Philippine texts Efmer E. Agustin The mountain writesback in Cordillera fiction : reading Rocky Cajigan's short stories as bioregional literature L.A. Piluden [De]spectacularizingport-disaster Tacloban : reading Victor N. Sugbo's poems Marilou G. Morales Raptures and continuities : the post conciliar Catholi literary imagination in the selected works of Carlos Aureus Isaiah F. Garcia Panangsirig ken panangsamira kadagiti sarigilap : exploring the emergence, structural features, characteristics, and prevailing themes of Ilocano flash fiction Rommel Amistad Pascua Hexagons & heptapods : alien encounters in Jose Ma. Espino's & Ted Chiang's SF Tilde Acuña Ang kiskisan, eskatolohiya at pahiwatig ng simuling-suling na kaluluwa ni Issmael, pangunahing tauhan ng "Sa piling ng mga bituin" ni Rogelio L. Ordoñez ayon sa mga dalumat ng tradisyong Vedik sa yugto ng pagkagumon (rapture) Abet Umil The use of revenge narrative in Alma Anonas-Carpio's Azucena Raymond G. Falgui Of gimmicks in bikol society : articulating contemporary experience through bikol prose Ma. Cienna A. Jaucian Coping humor in Bob Ong's ang alamat ng gubat and Kapitan Sino Alma Cita S. Calimbo
Includes bibliographical references.
Keywords: National Commission for Culture and the Arts -- National Committee on Literary Arts; Philippine literature -- 21st century -- Congresses; COVID-19 Pandemic, 2020- , in literature